Debt Relief for the Poorest : An Evaluation Update of the HIPC Initiative - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This study evaluates progress under the HIPC initiative since the 2003 evaluation of the Independent Evaluation Group. It finds that the Enhanced HIPC initiative (the Initiative for Heavily Indebted Poor Countries) cut debt ratios in half for 18 countries, but in eight of these countries, the ratios have come to once again exceed HIPC thresholds. Debt reduction alone is not a sufficient instrument to affect the multiple drivers of debt sustainability. Sustained improvements in export diversification, fiscal management, the terms of new financing, and public debt management are also needed, measures that fall outside the ambit of the HIPC initiative.